The rustic turn during late socialism and the popular movement against Soviet rule. Issue 1 (2nd January 2023) - Davoliūtė, Violeta; Rudling, Odeta
ABSTRACT: The success of mass mobilization in Lithuania against Soviet rule in the late 1980s can be attributed in part to the spread of the ethnocultural movement in the post-Stalin era. Characterized in this paper as the "rustic turn, " it began in the late 1950s with the Soviet-wide rehabilitation of kraevedenie (local area studies), part of Khrushchev's effort to rejuvenate grassroots political participation across the USSR. In Soviet Lithuania, the rehabilitation of kraštotyra had the unintended consequence of restoring nation-building practices from the interwar period and reintegrating individuals repressed under Stalin into public life. Rather than shaping Soviet subjects, the ethnocultural movement developed rituals of transformation that imbued the rustic ethnic past, not the Soviet future, with the aura of sacrality. Ostensibly apolitical, the movement nevertheless cultivated strong associative ties among citizens from various walks of life. With the outbreak of free discussion under glasnost, mass gatherings built upon the rituals of the ethnocultural movement to generate a community of affect grounded in nostalgia for a lost, mythical past and the trauma of displacement under the Soviet regime.